Study on the Buffering Effect of Physical Exercise on College Students’ Psychological Stress - Huang, Yanqin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the face of stressful events beyond their own coping scope or negative evaluation, individuals will experience pressure and negative emotions will increase. Therefore, it is a very important research topic to adopt effective ways to adjust college students to correctly face psychological pressure and negative emotions, so as to promote their physical and mental health. Studies have shown that physical exercise, as a way of regulation, can promote mental health and individual mood. Most of the previous studies adopted transverse studies, and the follow-up studies were relatively limited, ignoring the changes at the individual level. A research method is designed to study the buffering effect of physical exercise on psychological stress of college students. To begin, study objectives and techniques are chosen, and descriptive statistics are computed. Second, the correlation coefficients of psychological pressure, negative mood, and physical activity among college students are compared and studied to complete the buffer effect research. The application value of the cushioning effect research technique is shown by the practical example analysis, which indicates that it can properly represent the cushioning impact of physical exercise on college students' psychological strain.